Chloroplast: The Emerging Battlefield in Plant–Microbe Interactions - Yang, Feng; Xiao, Kunqin; Pan, Hongyu; Liu, Jinliang (Frontiers in Plant Science, 2021)
Higher plants and some algae convert the absorbed light into chemical energy through one of the most important organelles, chloroplast, for photosynthesis and store it in the form of organic compounds to supply their life activities. However, more and more studies have shown that the role of chloroplasts is more than a factory for photosynthesis. In the process of light conversion to chemical energy, any damage to the components of chloroplast may affect the photosynthesis efficiency and promote the production of by-products, reactive oxygen species, that are mainly produced in the chloroplasts. Substantial evidences show that chloroplasts are also involved in the battle of plants and microbes. Chloroplasts are important in integrating a variety of external environmental stimuli, and regulate plant immune responses by transmitting signals to the nucleus and other cell compartments through retrograde signaling pathways. Besides, chloroplasts can also regulate the biosynthesis and signal transduction of phytohormone including salicylic acid and jasmonic acid to affect the interaction between the plants and microbes. Since chloroplasts play such an important role in plant immunity, correspondingly, chloroplasts have become the target of pathogens. Different microbial pathogens target the chloroplast and affect its functions to promote their colonization in the host plant.